The Peculiarities of Chronotope in Don DeLillo’s Novel “Falling Man” - Asatryan, Ella (Armenian Folia Anglistika, 2012)
The article analyses the Falling Man by famous American writer Don DeLillo. The novel reflects the American society after the terrorist act 9/11 in 2001 not excluding the possibility of the repetition of the tragic event in any other place at any other time. The 9/11 divided the world into two parts – Before 9/11 and After 9/11. The novel rests on this division and makes it possible to consider the qualitative changes between the notions of time and space and confirms the unity of all time and space dimensions.